Role of levonorgestrel releasing intra-uterine system in the treatment of menorrhagia due to dysfunctional uterine bleeding and fibroid uterus - Gupta, Reena; Dewan, Rupali; Mittal, Pratima; Suri, Jyotsna; Dewan, Abhinav; Bharti, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was carried out to assess the clinical effectiveness of levonorgestrel releasing intrauterine device (LNG-IUS) in the treatment of menorrhagia due to either Dysfunctional Uterine Bleeding (DUB) or fibroid in Indian patients, and to assess patient satisfaction with this treatment modality. Methods: Sixty women with menorrhagia, 30 due to fibroid and 30 due to DUB, meeting inclusion criteria, received LNG-IUS and were prospectively followed up for 9 months with periodic clinical assessments and transvaginal ultrasounds. Patient satisfaction was assessed on a five-point scale. Results: One patient in DUB group was lost to follow-up. In DUB patients, the treatment failure rate was only 3.4% (1 out of 29 patients). The median PBAC score reduced by 95% at 9 months. Fibroid patients also had an equally impressive 97.7% reduction of PBAC score at 9 months, although the failure rate was higher (23.3%; 7 out of 30). Majority of patients were either ‘very satisfied’ or ‘satisfied’ with the treatment, although this percentage was more in DUB (82.8%) than in the fibroid group (66.7%). Haemoglobin and serum ferritin levels significantly increased in both groups. No major side effect was noted. Conclusions: LNG-IUS is an excellent treatment modality for patients of DUB, with good patient satisfaction. It is also a useful treatment option in non-submucosal small fibroids for the symptoms of menorrhagia, can reduce uterine volume and can help avoid hysterectomy, but there is no effect on fibroid volume. Majority of patients are satisfied, although satisfaction rates are less than in DUB patients.